2014
DOI: 10.1111/ijn.12273
|View full text |Cite
|
Sign up to set email alerts
|

The study of perceived stress, coping strategy and self‐efficacy of Chinese undergraduate nursing students in clinical practice

Abstract: The aim of the study was to explore the coping strategy and the effects of self-efficacy of Chinese undergraduate nursing students when they face the stress in clinical practice. Convenience sampling was used to recruit undergraduate nursing students in Mainland China who have practiced 3 months in hospitals in their final college year. Self-report questionnaires including demographics, Perceived Stress Scale, coping behaviour inventory and Generalized Self-Efficacy Scale were collected. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
134
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 23 publications
12
134
0
12
Order By: Relevance
“…The current study showed that the most common source of stress faced by nursing students is assignments and workload. This is consistent with the results of other studies [18,30]. The 4-year Bachelor of Nursing program in Hail University consists of 135 credit hours, among which 36 credit hours (72 actual hours) are clinical training.…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that the most common source of stress faced by nursing students is assignments and workload. This is consistent with the results of other studies [18,30]. The 4-year Bachelor of Nursing program in Hail University consists of 135 credit hours, among which 36 credit hours (72 actual hours) are clinical training.…”
Section: Discussionsupporting
confidence: 92%
“…; Zhao et al. ). Of the studies reporting emotional‐focused coping, seeking support from family and friends was cited as the most common styles utilized (Clark et al.…”
Section: Resultsmentioning
confidence: 98%
“…; Zhao et al. ). For example, in two separate studies in Spain, students scored avoidance behaviours such as avoiding difficulties during clinical practice, to quarrel with others, losing temper and avoiding teachers as their means of managing stressful events (Fornés‐Vives et al.…”
Section: Resultsmentioning
confidence: 98%
“…We have chosen the following variables to be predicted in the regression analysis: self-concept clarity, purpose in life and generalized self-efficacy -all linked to optimal functioning (e.g. : Emery, Walsh, & Slotter, 2015;Van Dijk et al, 2014;Ryff & Singer, 1998;Prairie, Scheier, Matthews, Chang, & Hess, 2011;Zhao, Lei, He, Gu, & Li, 2015).…”
Section: Introductionmentioning
confidence: 99%